Evaluation of cut-off values in acute paracetamol overdose following the United Kingdom guidelines - Hyun Ho Jeong; Kyungman Cha; Kyoung Ho Choi; Byung Hak So (BMC, 2022)
Abstract Background The United Kingdom guideline for acute paracetamol overdose has recommended the use of '100-treatment line'. Emergency medical centers in some developing countries lack the resources for timely reporting of paracetamol concentrations, hence treatment depends on reported dose. This study aimed to examine whether using an reported dose is safe to predict concentration above the 100-line. Methods Data were retrieved from two emergency medical centers retrospectively, between 2010 and 2017. The inclusion criteria were single acute paracetamol overdose, presentation within 15 h, and age ≥ 14 years. Multiple linear regression was performed to determine the effect of ingested dose on paracetamol concentration. Subgroups were created based on ingested dose, rate of concentration above 100-line were investigated. Results One hundred and seventy-two patients were enrolled in the primary analysis; median dose was 133.3 mg/kg and 46 (37.8%) had concentration above 100-line in the first test. Only dose per weight was moderately correlated with the first concentration (R2 = 0.410, p < 0.001). In the ≤200 mg/kg ingestion group, 18 patients showed concentration above 100-line and 8 showed acute liver injury. The cut-off value of 150 mg/kg showed 82.6% sensitivity and 73.8% specificity to predict concentration above 100-line. Conclusion Where paracetamol concentration is not available and activated charcoal is readily used, following United Kingdom guideline, it is safe to use an ingested dose of > 150 mg/kg as the cut-off value for N-acetylcysteine treatment with risk stratification for hepatotoxicity if the patient is ≥14 years and visit the ED within 15 h after an acute paracetamol overdose.